Hubungan Antara Perhatian Orang Tua Menurut Peserta Didik Dengan Minat Belajar Peserta Pada Pembelajaran Alquran Di TPQ - Handayani, Utari; Wirdatul'aini, Wirdatul'aini (Jurnal Family Education, 2022)
This research was motivated by the low interest in learning of students in learning the Koran at TPQ Mushola Nurul Ikhlas Bukik Kaciak Kampung Benteng Nagari Duku. The low interest in learning is thought to be caused by the low attention of parents according to students. The research aims to describe students' interest in learning, describe parental attention according to students, and see the relationship between parental attention according to students and participants' learning interest in learning the Koran at TPQ at Nurul Ikhlas Bukik Kaciak Mosque. This type of research is quantitative research with correlational type. The population in this study were TPQ participants in learning the Koran and the sample was taken by random sampling technique. Data collection techniques in the form of closed interviews and data collection tools in the form of questionnaires.The data analysis technique used the percentage formula and Spearman rho correlation. The results showed that parental attention according to students was categorized as low, students' interest in learning the Koran at TPQ Mushola Nurul Ikhlas Bukik Kaciak was categorized as low, and there was a significant relationship between parental attention according to students and students' interest in learning the Koran. at the TPQ at the Nurul Ikhlas Bukik Kaciak Mosque, Kampung Benteng Nagari Duku, Koto XI Tarusan District, Pesisir Selatan Regency. It is recommended that TPQ managers and educators at the Nurul Ikhlas Bukik Kaciak Kampung Benteng Mosque in order to increase student interest in learning, then can improve things that are deemed necessary to improve learning.